Protective effects of Mucuna pruriens seed extract pretreatment against cardiovascular and respiratory depressant effects of Calloselasma rhodostoma (Malayan pit viper) venom in rats - Fung, S.Y.; Tan, N.H.; Sim, S.M. (2010)
The protective effects of Mucuna pruriens seed extract (MPE) against the cardio-respiratory depressant and neuromuscular paralytic effects induced by injection of Calloselasma rhodostoma (Malayan pit viper) venom in anaesthetized rats were investigated. While MPE pretreatment did not reverse the inhibitory effect of the venom on the gastrocnemius muscle excitability, it significantly attenuated the venom-induced cardio-respiratory depressant effects (p<0.05). The protection effects may have an immunological mechanism, as indicated by the presence of several proteins in the venom that are immunoreactive against anti-MPE. However, we cannot rule out the possibility that the pretreatment may exert a direct, non-immunological protective action against the venom.